2020
DOI: 10.1093/ndt/gfaa174
|View full text |Cite|
|
Sign up to set email alerts
|

Using a generic definition of cachexia in patients with kidney disease receiving haemodialysis: a longitudinal (pilot) study

Abstract: Background Research indicates that cachexia is common among persons with chronic illnesses and is associated with increased morbidity and mortality. However, there continues to be an absence of a uniformed disease-specific definition for cachexia in chronic kidney disease (CKD) patient populations. Objective The primary objective was to identify cachexia in patients receiving haemodialysis (HD) using a generic definition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Previous studies have found that ACS has a high level of differentiation in patients with MHD cachexia. 27 However, this study not only further verifies this point but also comprehensively evaluates the reliability and validity of FAACT and its subscales. In terms of reliability (Table 2), Cronbach's alpha was acceptable, but PWB, EWB, and FWB had reliability of less than 0.74, whereas the overall FAACT and the ACS outperformed other disease detection instruments.…”
Section: Validitymentioning
confidence: 52%
“…Previous studies have found that ACS has a high level of differentiation in patients with MHD cachexia. 27 However, this study not only further verifies this point but also comprehensively evaluates the reliability and validity of FAACT and its subscales. In terms of reliability (Table 2), Cronbach's alpha was acceptable, but PWB, EWB, and FWB had reliability of less than 0.74, whereas the overall FAACT and the ACS outperformed other disease detection instruments.…”
Section: Validitymentioning
confidence: 52%
“…Some definitions of cachexia, and sarcopenia include measurement of physical activity, such as gait speed, or sit to stand ( Evans et al, 2008 ; Cruz-Jentoft et al, 2019 ; McKeaveney et al, 2021 ). However, these timed tests may be confounded in dialysis patients due to mineral bone disease and impracticable for the increasing number of wheelchair-bound dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…We measured self-reported energy expenditure, and although there was no difference in REE, however overall TEE was lower in frail patients, when active energy expenditure was determined. Other studies have used the Fatigue questionnaire (FACIT-F) ( McKeaveney et al, 2021 ), a 40-item measure that assesses self-reported fatigue and its impact upon daily activities and function. However, the results of this questionnaire can be confounded by fatigue secondary to anaemia and volume overload ( Yoowannakul et al, 2021 ), and psychological distress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These partly, but not entirely, overlapping syndromes (3,11) are part of a wide spectrum of nutritional and functional abnormalities in patients on HD, although an important common denominator appears to be tissue loss (11). Importantly, one of the criteria for the definition of PEW, also referred to as kidney cachexia, is an increase in inflammatory parameters (4,12). In contrast, inflammation is not included in the diagnostic criteria of sarcopenia (13).…”
Section: Clinical Syndromes Associated With a Loss Of MMmentioning
confidence: 99%